1997
DOI: 10.1007/bf03395253
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Delayed Effects of Imposed Postfeedback Delays in Computerized Programmed Instruction

Abstract: A recent study (Crosbie & Kelly, 1994) showed that brief externally imposed postfeedback delays improved performance in computerized programmed instruction. The present experiment extended that analysis by using shorter sessions, a more powerful single-subject design, and better timing measures, and by assessing maintenance of training effects. College students completed 40 sets of Holland and Skinner's (1961) programmed text on behavior analysis in a computerized format in a two-component multiple schedule. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…The present 10 % improvement is greater than the 8% obtained by Crosbie and Kelly (1994) and the 7% obtained by Kelly and Crosbie (1997) , and represents 28% of total possible improvement, which is virtually identical with the results obtained in those previous studies. Hence, the present training effect size is slightly better than those obtained in previous studies, and is impressive given effect sizes commonly reported in studies of educational improvement (Kelly & Crosbie, 1997;Kulik, Jaksa, & Kulik, 1978;Johnson & Ruskin, 1977).…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The present 10 % improvement is greater than the 8% obtained by Crosbie and Kelly (1994) and the 7% obtained by Kelly and Crosbie (1997) , and represents 28% of total possible improvement, which is virtually identical with the results obtained in those previous studies. Hence, the present training effect size is slightly better than those obtained in previous studies, and is impressive given effect sizes commonly reported in studies of educational improvement (Kelly & Crosbie, 1997;Kulik, Jaksa, & Kulik, 1978;Johnson & Ruskin, 1977).…”
Section: Discussionsupporting
confidence: 92%
“…Given previous results with imposed postfeedback delays (Crosbie & Kelly, 1994;Kelly & Crosbie, 1997), the most obvious explanation for how punishment improved performance is that it slowed subjects' responding so that more study time was available. The significant increases in questionresponse time (where questions were read) and score-question time (where questions, responses, and correct answers were displayed simultaneously) provide evidence of convergent validity for that explanation.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations